The dating and provenance of glass artefacts excavated from the ancient city of Tall Zirā‛a, Jordan - Kemp, Victoria; Schmidt, Katharina; Brownscombe, Will; Soennecken, Katja; Vieweger, Dieter; Häser, Jutta; Shortland, Andrew J. (Wiley, 2020)
The first deliberate manufacture of glass occurs in the sixteenth century BC, although the origin of the material is still a focus of debate; Egypt or Mesopotamia being the most likely innovator. The conventional approach is that glass technology first developed in Mesopotamia (Barag, 1970, p131-4; Moorey, 1994, p192; Shortland et al., 2017) and that the subsequent transfer to Egypt could be ascribed to tribute associated with the successful military campaigns in the Levant by the Egyptian king, Tuthmosis III (1479-1425 BC). Although there is textual and iconographic evidence for the production, supply and transport of glass between Egypt, its vassal Levantine states and Mesopotamia, it is very rare to find Egyptian glass in Mesopotamia or vice versa (Walton et al. 2009). The exceptions to date are two green glass rods found in Amarna, Egypt, which have trace element compositions consistent with Mesopotamian glass, and a collection of blue glass beads and a scarab recovered from a tomb in Gurob, Egypt, which also showed compositional consistency with glasses of known Mesopotamian origin (Varberg et al., 2016; Kemp, McDonald, A and Shortland, 2017; Kemp et al., 2019